Internal Tides Energy Transfers and Interactions with the Mesoscale Circulation in Two Contrasted Areas of the North Atlantic - Bella, Adrien; Lahaye, Noé; Tissot, Gilles (HAL CCSD)
International audience Abstract The energy budget of the internal tide and its life cycle is investigated with a high resolution numerical simulation and a vertical normal mode decomposition. Two areas of interest are considered: the Azores Islands over the mid Atlantic ridge and the Gulf Stream offshore the North of the US East coast shelf break. Low mode (1 and 2) internal tides are found to propagate from 100 km (mode 2) to 1000 km (mode 1) away from their generation sites. Waves loose a significant portion of their energy as they propagate through the Gulf Stream, in contrast to the Azores domain. In the Gulf Stream domain, the mesoscale circulation is responsible for energy transfers from low to high modes internal tides, while the topographic scattering is dominant in the Azores area. This transfer of energy toward high modes favours energy dissipation. The mesoscale is significant in the energy budget of modes higher than mode 1 for both domains, and for all baroclinic modes in the Gulf Stream area. The internal tide is found to extract or loose energy toward the mesoscale circulation, but this accounts for less than 14%, of the energy scattered from low internal tide modes to higher ones once summed over all contributions of the modal energy budget.